Product Attributes Determine The Preference of Herbal Medicine Consumers - Himmatul Miftah; Ita Novita; H Tsuwaibah; M. A. Sunaryo (Universitas Djuanda, 2020)
Abstract: The emergence of a wide variety of herbal medicinal products requires marketers to better understand consumer behavior. The various brands offered make consumers tend to have certain preferences before making a purchase decision. This study aims to determine the attributes of herbal medicinal products that determine the level of consumer preference in the purchasing process and the closeness of the attributes to consumer preferences. The method used is interviews with consumers which are then processed with conjoint analysis to determine the attributes that are most important to consumers in making a purchase. The research concludes that the most important attributes in purchasing herbal medicine in order from the most important are the properties, price, expiration time and packaging. There is a close relationship between the combination of attributes studied and consumer preferences for herbal medicine. This study is limited to four attributes and does not use ranking ratings on the stimulus or combination of attributes, consumer behavior. The uniqueness of this study is to analyze the attributes simultaneously. Keywords: Herbal medicine product attributes, consumer preferences, conjoin analysis, level of importance